Prvi koraci ka relevantnoj analizi uzroka i ishoda kosovske krize. Nad knjigom Petra Ristanovića Kosovsko pitanje 1974–1989. - Jan Pelikan (Токови историје, 2022)
The paper presents a review of the book by Petar Ristanović, Kosovsko pitanje 1974–1989 (The Kosovo Question 1974–1989). The results of Ristanović‘s work are placed in the context of previous knowledge on this topic.